Vietnam’s Hedging Strategy in the US–China Trade War: Geo-economic Response During the First Trump Administration - Fatharani, Fitri; Choiruzzad, Shofwan Al Banna (Global South Review, 2025)
The United States–China trade war placed Vietnam in a strategic yet vulnerable position, as a non-involved country that significantly benefited from trade and investment relocation. This situation contributed to Vietnam’s relative capability growth and created new space for asserting its role in regional economic and political structures. This article analyzes Vietnam’s foreign policy strategy in response to the rivalry between two great powers by applying a geo-economic approach and qualitative research methods. The findings reveal that Vietnam adopts a hedging strategy by undertaking active neutrality, contradictory policy—simultaneously accepting and rejecting dominance—and by diversifying its global partnerships to preserve policy autonomy. Vietnam’s hedging reflects both a function of national interest protection and an effort to leverage the opportunity created by relative capability enhancement amidst structural uncertainty. Thus, hedging emerges as a relevant geo-economic instrument for middle states in navigating major power competition while maintaining strategic space and sovereign decision-making.